The Impact of The Israeli Product Boycott on The International Economy, The Israeli Product Boycott Movement: Economic, Legal, and Ethical Perspectives - Puspita, Indah Lia; Yahya, Ahmat; Adha, Nur Alif Khairila Al Ahmad; Juliandari, Winda (LPPM STIE KRAKATAU, 2025)
This research is based on the Israeli-Palestinian war that has an impact on the international economy, in the form of a petition to boycott products originating from Israel. Boycott has the meaning of a movement not to buy or use products produced by Israeli companies or parties considered pro against Israel's actions towards Palestinians. This study uses case study examples that occurred in developed and developing countries. In developed countries such as China, the impact is seen on investment cultivation which is characterized by a shift in investment priorities, where China may shift its investment to other sectors or countries that are more stable and free from the risk of boycotts. In developing countries such as Indonesia, PT Unilever Tbk experienced a decline in sales which resulted in mass layoffs and increased unemployment. The boycott action also has a positive impact on developed countries, such as increasing the use and purchase of domestic products, the growth of small and medium enterprises (MSMEs), the improvement of the local economy, and the creation of jobs. In developing countries, this action also has a positive impact in the form of shifting consumption patterns and increasing humanitarian solidarity. This study uses a descriptive qualitative method to determine the positive and negative aspects of the petition to boycott Israeli products.